2022
DOI: 10.1001/jamaneurol.2022.0245
|View full text |Cite
|
Sign up to set email alerts
|

Omicron-Specific Cytotoxic T-Cell Responses After a Third Dose of mRNA COVID-19 Vaccine Among Patients With Multiple Sclerosis Treated With Ocrelizumab

Abstract: IMPORTANCEThe SARS-CoV-2 variant B.1.1.529 (Omicron) escapes neutralizing antibodies elicited after COVID-19 vaccination, while T-cell responses might be better conserved. It is crucial to assess how a third vaccination modifies these responses, particularly for immunocompromised patients with readily impaired antibody responses.OBJECTIVE To determine T-cell responses to the Omicron spike protein in anti-CD20-treated patients with multiple sclerosis (MS) before and after a third messenger RNA COVID-19 vaccinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
73
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 13 publications
13
73
1
Order By: Relevance
“…We established that a third vaccination induces a recall of SARS-CoV-2 T cells in OCR-treated patients but does not further increase circulating SARS-CoV-2 T-cell numbers compared with after the second vaccination. This is in agreement with recent studies describing a T-cell recall after the third vaccination, 2 , 3 which was similar compared with the second vaccination for both OCR-treated patients and healthy controls. 2 T-cell responses induced by the vaccine have been demonstrated to be only minorly compromised to variants of concerns, including Omicron, both in healthy controls 4 as in OCR-treated patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We established that a third vaccination induces a recall of SARS-CoV-2 T cells in OCR-treated patients but does not further increase circulating SARS-CoV-2 T-cell numbers compared with after the second vaccination. This is in agreement with recent studies describing a T-cell recall after the third vaccination, 2 , 3 which was similar compared with the second vaccination for both OCR-treated patients and healthy controls. 2 T-cell responses induced by the vaccine have been demonstrated to be only minorly compromised to variants of concerns, including Omicron, both in healthy controls 4 as in OCR-treated patients.…”
Section: Discussionsupporting
confidence: 93%
“… 2 T-cell responses induced by the vaccine have been demonstrated to be only minorly compromised to variants of concerns, including Omicron, both in healthy controls 4 as in OCR-treated patients. 3 …”
Section: Discussionmentioning
confidence: 99%
“…The screening process is illustrated in the PRISMA flowchart in Figure 1 . Of these studies, there were 12 observational studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], one randomised-controlled trial [ 33 ], and four case series [ 34 , 35 , 36 , 37 ]. The key trial characteristics of each included study are reported in Table 1 , with a comparison of the characteristics of the studies included in the meta-analysis in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the context of COVID-19, whether antibody production is the appropriate or sole immune correlate of protection is currently unknown and the role of T or B cell-mediated immunity for effective clinical protection requires additional investigations. Available data report impaired humoral response to SARS-CoV-2 infection or vaccines in ocrelizumab treated patients, but induced robust cellular response ( 28 35 ), significantly boosted after a third vaccine dose ( 36 ), or preserved against SARS-CoV-2 Delta or Omicron variants ( 37 ). Despite the impaired humoral immune response to SARS-CoV2 infection or vaccine, no known correlation with clinical severity has been established, as compensatory cellular-mediated immune response could provide protection against serious complications from COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%